Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/tri.13342
|View full text |Cite
|
Sign up to set email alerts
|

Dual aortic and portal perfusion at procurement prevents ischaemic-type biliary lesions in liver transplantation when using octogenarian donors: a retrospective cohort study

Abstract: Several risk factors for ischaemic-type biliary lesions (ITBL) after liver transplantation (LT) have been identified, but the role of portal vein perfusion at graft procurement is still unclear. This was a prospective study on double aortic and portal perfusion (DP) of liver grafts stratified by donor's decade (<60 yo; 60-69 yo; 70-79 yo and ≥80 yo) versus similar historical cohorts of primary, adult grafts procured with single aortic perfusion (SP) only. The primary study aim was to assess the role of DP on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Others postulated that ischemic cholangiopathy (IC) might be predicted by a bile pH <7.4. In agreement with Watson et al, we believe that bile production and pH is a complex process dependent on the integrity of many facets of liver function, but several other parameters may play a fundamental role in the development of IC such as the type of donor (DCD versus DBD), the warm ischemia time, or the procurement technique (single versus dual perfusion) …”
Section: Discussionsupporting
confidence: 91%
“…Others postulated that ischemic cholangiopathy (IC) might be predicted by a bile pH <7.4. In agreement with Watson et al, we believe that bile production and pH is a complex process dependent on the integrity of many facets of liver function, but several other parameters may play a fundamental role in the development of IC such as the type of donor (DCD versus DBD), the warm ischemia time, or the procurement technique (single versus dual perfusion) …”
Section: Discussionsupporting
confidence: 91%
“…As a consequence, HCC candidate seemed to be the most suitable candidate for elderly grafts since they usually present compensated liver disease. These policies are also supported by the contribution of machine perfusion, which reduces the risk of primary nonfunction of ECD grafts by improving the quality of conservation and reducing the consequences brought on by ischaemia-reperfusion [26]. However, the present study has some limitations.…”
Section: Discussionmentioning
confidence: 91%
“…(33) Other technologies such as ex vivo machine perfusion appear, at this time, to be more feasible and readily applicable as a potential evaluation and reconditioning tool. (34,35) Studies for renal transplantation have shown hypothermic perfusion to be superior to static cold storage in outcome and costs. (36,37) We are not of aware of any such comparisons for liver transplantation at time of writing.…”
Section: Discussionmentioning
confidence: 99%